Unlocking nerve regeneration: electrical stimulation and bioscaffolds to enhance peripheral nerve regeneration - Thakkar, Vanshit; Mehdipour, Melod; Chang, Stephano (Frontiers in Neuroscience, 2025)
Peripheral nerve injury (PNI) is a challenging clinical problem resulting in disabling sensorimotor deficits, which may become permanent if recovery does not take place in a timely manner. In this review, we examine recent insights into key molecular mechanisms—particularly MAPK/ERK and PI3K/Akt—that govern Wallerian degeneration, Schwann cell (SC) reprogramming, and macrophage polarization. These and other critical steps in the axonal regeneration process must be understood and navigated for a therapeutic approach to be successful. We highlight emerging therapeutic strategies, such as electrical stimulation (ES), which appears to work by activating many of these pro-regenerative gene networks, both in neurons and non-neuronal support cells. Advances in biomaterial engineering, including natural and synthetic scaffolds enriched with growth factors, also show promise in facilitating axonal regeneration across nerve gaps. We postulate that integrating optimized ES protocols with innovative scaffold designs will allow for synergies to further enhance axonal regeneration and functional recovery.